Experimental characterization of natural fibre–soil interaction: lessons for earthen construction - Vincenzini, Alessandra; Augarde, Charles E.; Gioffrè, Massimiliano (Materials and structures, 2021)
Earthen construction materials are the subject of renewed interest due to the rising alarm about environmental pollution from the construction industry. Current research efforts are focused on improving the mechanical properties of earthen materials to make them modern and competitive. To increase strength and improve ductility fibres can be added to the soil mixture and if natural fibres are used one achieves stabilisation in an environmentally friendly way. Several previous studies have dealt with the behaviour of this composite material at a macroscopic level and on the general interaction between fibres and soil, but there is little published research on the interfacial mechanical interaction between natural fibre reinforcement and a soil matrix which is key to the former. This paper attempts to fill this gap by presenting and discussing laboratory results from a large campaign of pull-out tests conducted on composite earthen samples. The variables investigated here are the nature of the fibres (i.e. single or collections twisted together) and the use of fibre treatments such as PVA glue and baking soda. In the study both fibre–soil failure and soil-soil failure are investigated and the results lead to conclusions as to appropriate use of fibres to reinforce earthen construction materials.